Alanine based coordinating ligand mediated hydrothermal synthesis of CuS nano/microstructures and morphology dependent photocatalysis1. Issue 18 (14th May 2015) - Vinod Kumar, V.; Hariharan, P. S.; Eniyavan, D.; Hari, Natarajan; Anthony, Savarimuthu Philip
<x xml:space="preserve">Abstract</x> Coordinating ligand controlled CuS nano/microstructures and morphology dependent photocatalysis.